Impact of Porphyrin Binding to GENOMES UNCOUPLED 4 on Tetrapyrrole Biosynthesis in planta - Fölsche, Vincent; Großmann, Christopher; Richter, Andreas S. (Frontiers in Plant Science, 2022)
Plant tetrapyrrole biosynthesis (TPS) provides the indispensable chlorophyll (Chl) and heme molecules in photosynthetic organisms. Post-translational mechanisms control the enzymes to ensure a balanced flow of intermediates in the pathway and synthesis of appropriate amounts of both endproducts. One of the critical regulators of TPS is GENOMES UNCOUPLED 4 (GUN4). GUN4 interacts with magnesium chelatase (MgCh), and its binding of the catalytic substrate and product of the MgCh reaction stimulates the insertion of Mg2+ into protoporphyrin IX. Despite numerous in vitro studies, knowledge about the in vivo function of the GUN4:porphyrin interaction for the whole TPS pathway, particularly in plants, is still limited. To address this, we focused on two highly conserved amino acids crucial for porphyrin-binding to GUN4 and analysed GUN4-F191A, R211A, and R211E substitution mutants in vitro and in vivo. Our analysis confirmed the importance of these amino acids for porphyrin-binding and the stimulation of plant MgCh by GUN4 in vitro. Expression of porphyrin-binding deficient F191A, R211A, and R211E in the Arabidopsis gun4-2 knockout mutant background revealed that, unlike in cyanobacteria and green algae, GUN4:porphyrin interactions did not affect the stability of GUN4 or other Arabidopsis TPS pathway enzymes in vivo. In addition, although they shared diminished porphyrin-binding and MgCh activation in vitro, expression of the different GUN4 mutants in gun4-2 had divergent effects on the TPS and the accumulation of Chl and Chl-binding proteins. For instance, expression of R211E, but not R211A, induced a substantial decrease of ALA synthesis rate, lower TPS intermediate and Chl level, and strongly impaired accumulation of photosynthetic complexes compared to wild-type plants. Furthermore, the presence of R211E led to significant growth retardation and paler leaves compared to GUN4 knockdown mutants, indicating that the exchange of R211 to glutamate compromised TPS and Chl accumulation more substantially than the almost complete lack of GUN4. Extensive in vivo analysis of GUN4 point mutants suggested that F191 and R211 might also play a role beyond porphyrin-binding.